1997
DOI: 10.1172/jci119278
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and dexamethasone stimulate calcineurin activity through a transcription-independent mechanism involving steroid receptor-associated heat shock proteins.

Abstract: Heat shock proteins (HSP) are components of the steroid receptor complex and are released into the cell cytosol after hormone binding. We tested whether HSPs released from steroid receptors mediate an increase in calcineurin phosphatase activity by steroid hormones. Aldosterone increased calcineurin activity in microdissected rat cortical collecting ducts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…The mineralocorticoid receptor is a protein complex that includes a steroid-binding protein receptor and heat shock proteins (Hsps) of 56, 70, and 90 kDa. Interestingly, Tumlin et al (67) reported that when steroid hormone bound to its receptor, the release of the Hsps complex is able to activate calcineurin phosphatase activity. Also, it has been demonstrated that calcineurin might regulate Na ϩ -K ϩ -ATPase activity through dephosphorylation of its catalytic subunit (30).…”
Section: Role Of Aldosterone In Csa Nephrotoxicitymentioning
confidence: 99%
“…The mineralocorticoid receptor is a protein complex that includes a steroid-binding protein receptor and heat shock proteins (Hsps) of 56, 70, and 90 kDa. Interestingly, Tumlin et al (67) reported that when steroid hormone bound to its receptor, the release of the Hsps complex is able to activate calcineurin phosphatase activity. Also, it has been demonstrated that calcineurin might regulate Na ϩ -K ϩ -ATPase activity through dephosphorylation of its catalytic subunit (30).…”
Section: Role Of Aldosterone In Csa Nephrotoxicitymentioning
confidence: 99%
“…Tumlin et al, 1997;Cissel and Beaven, 2000). These are yet ill-understood and I will not discuss them in further detail.…”
Section: Inhibition Of Signal Transductionmentioning
confidence: 99%
“…Moreover, several rapid aldosterone-induced changes of the concentration of intracellular second messengers have been described. 6,10,11 Aldosterone is reported to activate protein kinase C (PKC) in distal colon cells and cultured kidney cells and to decrease its activity stimulated by phorbol-12-myristate-13-acetate in rat neonatal cardiomyocytes. [12][13][14] However, there is no clear consensus whether PKC is involved in the nongenomic effects of aldosterone on the vascular tone of coronary arteries in the ischemic hearts.…”
mentioning
confidence: 99%